’’ملتِ بیضا پر ایک عمرانی نظر‘‘ ،اور ’’ خطبہ الہ آباد‘‘ ۔۔ مشترک نکات کا جائزہ - ڈاکٹر محمد آصف; ڈاکٹر محمد اشرف (Khayaban - خیابان, 2025)
This paper explores the intellectual evolution of Allama Muhammad Iqbal’s political philosophy by examining two of his seminal works i.e. The Muslim Community: A Social Study (Millat-e-Beiza par Aik Umarani Nazar) (1910) and Allahabad Address (Khutbah Allahabad (1930). The study highlights the shared ideological themes between these texts, tracing the development of Iqbal’s thought from its early philosophical formulation to its mature political expression. Central to both works is the affirmation of a distinct Muslim identity, the articulation of Islamic nationalism and the call for the revival of the Muslim Ummah. The study argues that Millat-e-Beiza serves as both a conceptual and literary precursor to the Allahabad Address, establishing the foundational ideas that would later culminate in the demand for Pakistan. Iqbal’s use of symbolic language, rhetorical strategy and ideological framing reflects a convergence of literary style and political conviction. This paper contributes to Urdu literary scholarship by demonstrating how Iqbal’s work functions as a vehicle for socio-political transformation and ideological continuity.